Avaliação da atividade proliferativa do epitélio mamário após a utilização de três ciclos de anticoncepcional hormonal combinado oral - Fenile, Rogerio [UNIFESP] (2016)
The most controversial aspect in relation to oral hormonal contraception is the risk of developing breast cancer. Knowledge of the factors that influence the proliferation of normal breast epithelium is essential to understanding carcinogenesis and proliferative activity can be assessed by various techniques, including the immunohistochemical analysis of Ki 67. In this work, we aim to compare the overall proliferative activity of breast after three cycles of combined oral contraceptive with a natural cycle and with that presented after only one cycle. Were selected 70 women attended in the period July 2006 to February 2007. These underwent excision of breast lump and breast tissue macroscopically regular adjacent to the node, lying this at least 1 cm. The patients were divided into two groups: group ACHO, consisting of 20 women using three cycles of combined oral contraceptive consisting of 150 ug levonorgestrel and 30 ug of ethinyl estradiol, and the group CN consisting of 40 women with natural cycles eumenorrheic, that not used any hormonal medication. Ten patients was excluded In the fourth month after initiation of use of the ACHO, the group ACHO patients were divided into four groups according to the use of the contraceptive. The ACHO1 group (5 patients) in the first week; ACHO2 (5 patients) in the second week; ACHO3 (5 patients) in the third week and the ACHO4 (5 patients), the break of the week. Results: The highest levels of Ki-67 count occurred in the third (16.66%) and fourth week (16.69 %) similar to one another. Additionally, it is noted that the average pause week count was greater than the first week (10.42%) and of the second week (8.52%), which in turn were not distinct. When comparing the use of 3 cycles with 1 cycle, we found that there was no difference in Ki-67 count levels by the time the first two weeks. However, note that the Ki-67 levels were higher in women who used contraceptives for longer both in the third week as the week's break. In conclusion, the proliferative activity of artificial cycle was significantly higher than the natural cycle, and after three cycles, showed higher rates of proliferation in the third and fourth weeks of the menstrual cycle.